Brand Community Knowledge, Involvement, Trust, Engagement, And Brand Loyalty (Glow Up Agents Community) - Andi Ade Rufiani RM; Maria Apsari Sugiat (Publikasi Indonesia, 2025)
The development of digital technology makes the brand community a key strategy to build loyalty in the beauty industry. This study examines the